Fun & games : stories science photos tell - Cobb, Vicki (New York : Lothrop, Lee & Shepard Books, 1991)
Examines in text and special, detailed photographs how popcorn pops, how a ball bounces, how a phonograph needle reads the sound on a record, what happens in the brain when one is listening to words and music, and many other things.
Keywords: Science -- experiments; Scientific recreations